Rock Marches in Lithuania in 1987–1989. A Glance at the Singing Revolution - Kuklytė, Birutė (Genocidas ir rezistencija, 2008)
Rock marches in Lithuania are unprecedented musical events which took place between 1987 and 1989. Rock groups performed their own music for thousand-strong audiences. The festivals followed traditions of the democratic world: the performers expressed their own attitude to what was happening in the country. The first march took place in 1987, which was a freedom march of young people and rock music. The last two festivals were more politicised. The 1988 rock march became a platform for the ideas of the Sąjūdis Revival Movement and the Greens, while in 1989 the closure of the Soviet military bases and plants was demanded, and the Ribbentrop-Molotov Pact was mentioned. Part of the proceeds from the concerts went to support public organisations (in 1987, the Lithuanian Culture Fund, in 1988, the Lithuanian Revival Movement, and in 1989, the Lithuanian Society for the Disabled). Over 150,000 people attended the three rock marches.
Keywords: rock music; Soviet perestroika; anti-Soviet resistance